Non-verbal Communication in the family (Journal of Parents and Teachers, 2014)
Looks and gestures say more than we think. Being aware of it will help us in our duty as parents. Physical contact and parents being role models to imitate are essential for a kid development. This article also talks about the importance of a good emotional communication as well as the active listening.
Keywords: school and family; education and family; non-verbal communication; respect; active listening.